Temperature Tuning the Catalytic Reactivity of Cu-Doped Porous Metal Oxides with Lignin Models - Bernt, Christopher M.; Manesewan, Hussaya; Chui, Megan; Boscolo, Mauricio [UNESP]; Ford, Peter C. (American Chemical Society (ACS), 2018)
Reported are the temperature dependencies of the temporal product evolution for lignin model compounds over copper-doped porous metal oxide (CuPMO) in supercritical-methanol (sc-MeOH). These studies investigated 1-phenylethanol (PPE), benzyl phenyl ether (BPE), dihydrobenzofuran (DHBF), and phenol over operating temperature ranges from 280 to 330 °C. The first three model compounds represent the β-O-4 and α-O-4 linkages in lignin as well as the furan group commonly found in the β-5 linkage. Phenol was investigated due to its key role in product proliferation as noted in earlier studies with this Earth-abundant catalyst. In general, the apparent activation energies for ether hydrogenolysis proved to be significantly lower than that for phenol hydrogenation, a major side reaction leading to product proliferation. Thus, temperature tuning is a promising strategy to preserve product aromaticity as demonstrated by the more selective conversion of BPE and PPE at lower temperatures. Rates of methanol reforming over CuPMO were also studied over the temperature range of 280-320 °C since it is this process that generates the reducing equivalents for this catalytic system. In the absence of substrate, the gaseous products H2, CO, and CO2 were formed in ratios stoichiometrically consistent with catalyzed methanol reformation and water gas shift reactions. The latter studies suggest that the H2 production ceases to be rate limiting early in batch reactor experiments but also suggest that H2 overproduction may contribute to product proliferation.
Keywords: Activation energies; Heterogenous catalysis; Lignin models; Methanol reforming; Supercritical methanol